Short-Duration Beta-Alanine Supplementation Did Not Prevent the Detrimental Effects of an Intense Preparatory Period on Exercise Capacity in Top-Level Female Footballers - Ribeiro, Rafael; Duarte, Breno; Guedes da Silva, André; Ramos, Guilherme Passos; Rossi Picanço, Andreia; Penna, Eduardo Macedo; Coswig, Victor; Barbalho, Matheus; Gentil, Paulo; Gualano, Bruno; Saunders, Bryan (Frontiers in Nutrition, 2020)
Purpose: High-intensity activity is an important aspect of football performance during competitive match play. The aim of this study was to investigate the effect of beta-alanine supplementation throughout a short-duration intense football-specific training period prior to an international competition on measures of high-intensity running performance. Methods: Twenty-four elite international U20 female footballers (age 18 ± 1 y, height 1.67 ± 0.07 m, body mass 62.7 ± 7.4 kg) volunteered to perform the YoYo Intermittent Recovery Test Level 1 (YoYo IR1), the Running Anaerobic Sprint Test (RAST) and a 20-m maximal sprint test on two separate occasions, separated by 3 weeks of training and supplementation. Participants were randomly assigned to receive either 6.4 g·day-1 sustained-release beta-alanine (BA, N=12) or an equivalent dose of maltodextrin (placebo, PL, N=12) throughout a 3-week standardised training camp. There was a main effect of group (P=0.05) and time (P=0.004) on YoYo IR1; overall values were lower in PL and distance covered was lower post- versus pre-supplementation. There was no group x time interaction (P=0.07). There was a time effect for RAST, but no further effects and no effects for the 20-m sprint. Conclusions: Top-level female footballers involved in this intense 3-week training period prior to a competition worsened their high-intensity intermittent exercise capacity, and this negative result was not attenuated by a short-duration BA supplementation protocol throughout the same period. Further work is necessary to elucidate whether adapted training protocols and BA dosing regimens could lead to better results.